Information technologies in the control system and monitoring credit operations as a tool of counteracting of the legalization (laundering) of incomes, received by criminal way - Маркарян, Г. О. (Problems of Informatization and Control, 2013)
This article presents the information technologies in the control system and monitoring credit operationsas a tool of counteracting of the legalization (laundering) of incomes, received by criminal way.The system analysis of banking activities by the primary financial monitoring and the realization ofmonetary policy is carried out, the structure of a control system and of a monitoring of credit operationsis offered, the decomposition of the system into five interrelated subsystems is carried out, foreach of subsystems the criteria for decision-making are formulated in the form of the objective functions,software is created. The solution of optimization problems with the using advanced informationtechnologies lead to objectify of the decisions of banks in the credit and financial policy, and contributesto strengthening the effectiveness of actions aimed at the prevention of crime in the credit andfinancial sphere.